Internal Marketing: Using Marketing-Like Approaches To Build Business Competencies And Improve Performance In Large Malaysian Corporations - M. Saad, Norizan; K. Ahmed, Pervaiz; Mohammed Rafiq, Mohammed Rafiq (Asian Academy of Management (AAM), 2002)
This study was conducted to make substantial progress in building theory about customer-focused organisations and its impact on business competencies and performance. To date, it is the first empirical attempt to gain knowledge on internal marketing (IM) implementation using a 'marketing-like' approach. The results of the study suggest that this approach is imperative to create organisational competencies and business performance. This study therefore serves to develop and test a conceptual model linking IM mix components, competencies and business performance that adds knowledge to the IM implementation framework in particular and other organisational development theories in general.